(untitled) (Research, Society and Development, 2021)
Breastfeeding is one of the most relevant ways to benefit the health of newborns, where milk provides benefits not only for the newborn, but also for the mother figure. In this sense, when certain factors occur that are harmful during this process, care must also take place in an agile way, obstacles related to maternal stress can be highlighted, especially when it is the mother’s first pregnancy. The nursing mother must receive professional help, seek whenever she is given the opportunity for information, be confident and open physically and emotionally. In this bias, the aim of this study is to analyze the role of nurses regarding the issue of guidance to promote breastfeeding adequately and without richness for mother and baby. This is a literature review.